A Privacy-Enhanced Scheme Within The Public Key Infrastructure For The Internet Of Things, Employing Elliptic Curve Diffie-Hellman (ECDH) - Sebbah, Abderrezzak; Benamar, Kadri (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
The Public Key Infrastructure (PKI) serves as the foundation for online security, particularly within the realm of the Internet of Things (IoT). It operates based on certified public keys that remain permanent but can be revoked when necessary, such as in the case of a change in ownership, compromise of the private key, or malicious activities. Although this method ensures secure key utilization with traceability, it also introduces a potential privacy risk due to the traceability and utilization of identity-based certificates. This approach is considered an innovative strategy for ensuring user confidentiality, integrity, authentication, and privacy in the context of the Internet of Things. The proposed solution integrates elliptic curves (ECDH) and traditional PKI to safeguard user privacy. It introduces two types of elliptic curve keys: long-term identity-based certified keys and dynamically generated temporary anonymous aliases. These aliases are seamlessly recorded by the certification authority, which maintains distinct directories for long-term and temporary keys. This dual-key approach enhances security while addressing the specific requirements of the Internet of Things.